Pemanfaatan Media Pembelajaran Berbasis Web Educaplay dalam Fluida Statis - Syahendra, Okta Farhan; Tebriani, Sylvina; Deswita, Pipi (Universitas Islam Negeri Imam Bonjol Padang, 2024)
The modern era has brought significant changes in various fields, including education, where information technology plays an important role in distance learning. Technology can facilitate flexible and interactive learning platforms. One innovation in education is the use of web-based games, such as Educaplay, which provides various interactive game features for learning. This research aims to explore the utilization of Educaplay web technology based on Froggy Jump game in physics learning related to static fluid material. The research method used is Research and Development (RnD) with the ADDIE model which includes analysis, design, and development. The results of the study describe the use of this game-based educaplay web in physics learning. Educaplay, with its interactive features, is able to increase students' interest and engagement in learning physics, overcoming the challenges of conventional learning that is often boring. However, the successful implementation of this technology requires the support of adequate facilities and infrastructure as well as teacher readiness in utilizing technology effectively.